3D printed guides for controlled alignment in biomechanics tests. Issue 3 (8th February 2016) - Verstraete, Matthias A.; Willemot, Laurent; Van Onsem, Stefaan; Stevens, Cyriëlle; Arnout, Nele; Victor, Jan
Abstract: The bone-machine interface is a vital first step for biomechanical testing. It remains challenging to restore the original alignment of the specimen with respect to the test setup. To overcome this issue, we developed a methodology based on virtual planning and 3D printing. In this paper, the methodology is outlined and a proof of concept is presented based on a series of cadaveric tests performed on our knee simulator. The tests described in this paper reached an accuracy within 3–4° and 3–4 mm with respect to the virtual planning. It is however the authors׳ belief that the method has the potential to achieve an accuracy within one degree and one millimeter. Therefore, this approach can aid in reducing the imprecisions in biomechanical tests (e.g. knee simulator tests for evaluating knee kinematics) and improve the consistency of the bone-machine interface.